2011
DOI: 10.1080/09540121.2011.555942
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of retention in care among adults infected with HIV in an urban clinic

Abstract: Adults infected with HIV live longer when they receive regular medical care, yet many adults are not retained in care. Providers measure retention in order to evaluate interventions to improve retention and quality of HIV care. However, multiple measures for retention exist. This study compares two methods of operationalizing retention and evaluates the contribution of individual characteristics on the likelihood of retention. A chart review was performed for a random sample of 212 active clients of an urban H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…14,[16][17][18][19] However, despite this finding, we found that, compared with women in care, both seekers and nonseekers were no more likely to perceive lack of health insurance as a barrier to care. Although prior studies have found drug use to be associated with poor engagement in care, 14,16,19,[21][22][23][24][25] we found that, compared with women in care, only non-seekers were more likely to report high-risk drug use and sexual behaviors. As this subgroup was less likely to report transportation as a barrier to care and was no more likely to report other structural barriers to care as women in care, our findings suggest that this subgroup of women may not report barriers because they are not actively seeking HIV medical care.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…14,[16][17][18][19] However, despite this finding, we found that, compared with women in care, both seekers and nonseekers were no more likely to perceive lack of health insurance as a barrier to care. Although prior studies have found drug use to be associated with poor engagement in care, 14,16,19,[21][22][23][24][25] we found that, compared with women in care, only non-seekers were more likely to report high-risk drug use and sexual behaviors. As this subgroup was less likely to report transportation as a barrier to care and was no more likely to report other structural barriers to care as women in care, our findings suggest that this subgroup of women may not report barriers because they are not actively seeking HIV medical care.…”
Section: Discussioncontrasting
confidence: 53%
“…We forced age and race/ethnicity into the multivariate models as these have been consistently associated with engagement in HIV care in previous studies. 6,17,[22][23][24][25] All analyses were conducted using SAS statistical software (SAS 9.2, SAS Institute, Inc., Cary, NC).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…24, 26, 9, 13, 29, 3035 Notably, patients with mood disorders and substance abuse have twice the odds of poor adherence to ART than patients without these conditions, 29, 3638 and patients with active substance abuse are half as likely to be adherent to HIV clinic visits. 39 …”
Section: Introductionmentioning
confidence: 99%
“…Alcohol abuse has been reported by up to 53% of adults with HIV (Galvan et al, 2002; and NCI ranging from asymptomatic neurocognitive impairment (ANI) to HIV-associated dementia (HAD) has been observed in about 37% of adult PLWH . Heavy alcohol use and NCI may have a negative synergistic effect on self-reported medication adherence and service utilization rates Marx, Malka, Ravishankar, & Schwartz, 2011;. Improving utilization of both HIV and substance abuse services is central to increasing treatment adherence and optimizing health outcomes for PLWH White House Office of National AIDS Policy, 2010).…”
Section: Chapter V Transition To Manuscriptmentioning
confidence: 99%